Kedudukan Harta Perkawinan Atas Nama Istri di Indonesia (Studi Putusan Pengadilan Negeri Jakarta Barat No. 330/Pdt.G/2012/Pn. Jkt Bar) - Tria Alvionita (Universitas Harapan Medan, 2022)
If the marriage is terminated due to divorce, the joint property is regulated according to their respective laws. If a husband and wife break up because of divorce, they embrace Islam, then the property of the marriage is divided according to Islamic law, but it does not rule out the possibility of dividing it based on customary law. The problem discussed is the regulation of marital property in the name of the wife according to the statutory regulations. The distribution of joint assets according to the decision of the West Jakarta District Court No. 330/Pdt.G/2012/PN. JKT Bar and the judge's legal considerations in the decision of the West Jakarta District Court No. 330/Pdt.G/2012/PN. JKT Bar. The type of research is normative juridical which is obtained from library materials that are descriptive analytical, namely to obtain a detailed and systematic description of the problems studied. The results of the study show that property acquired during the marriage period becomes joint property, as long as the goods are purchased in a marriage bond, the property becomes the jurisdiction of the joint property, who buys it, on whose name it is registered and where it is located does not matter. In Decision No. 330/Pdt.G/2012/PN. JKT BAR, because the distribution of joint assets is not regulated in the Marriage Law or in its Implementing Regulations, the panel of judges refers to the rules of the Civil Code Article 128 paragraph (1). Judge's legal considerations in Decision No. 330/Pdt.G/2012/PN. JKT BAR that the Plaintiff has been able to prove that the object of the dispute is the joint property of the Plaintiff and the Defendant, as long as there is no marriage agreement regarding joint property, all assets acquired during the marriage period are joint property.